Molybdenum supply and biological fixation of nitrogen by two Brazilian common bean cultivars - Alinne da Silva; Vinícius I. Franzini; Cristiano D. Piccolla; Takashi Muraoka (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The common bean has been considered to have low biological nitrogen fixation capacity; however, this process can be made more effective with molybdenum (Mo) supplementation. The objective of this study was to evaluate the influence of Mo rates on the growth and biological nitrogen fixation by two Brazilian common bean cultivars using the 15N isotope dilution technique. The experiment was performed in 2014 in a completely randomized design arranged in a 5 x 3 factorial scheme, corresponding to 5 rates of Mo (control, 40, 80, 120 and 240 g ha-1), the common bean cultivars Aporé, Ouro Negro and NORH-54 (a non-nodulating common bean cultivar), and three replicates. The application of Mo and the inoculation with rhizobia strains contributed to improving nitrogen fixation and grain weight. The cultivar Ouro Negro showed a higher number and weight of nodules and a higher amount of nitrogen derived from the atmosphere than the cultivar Aporé. The biological nitrogen fixation of Aporé was more dependent on the application of Mo. These results indicated that inoculation with Rhizobium strains and Mo supply effectively contributed to biological nitrogen fixation and improving grain production.